PEMEROLEHAN BAHASA PERTAMA UNTUK ANAK USIA 2 TAHUN (DALAM TATARAN FONOLOGI) DI DAERAH JAWA - Ridhaningtyas Wahyu Amanda (Universitas Sarjanawiyata Tamansiswa, 2020)
Acquisition of language is the occurrence of a person's way to speak or acquire a child's first language. There are three components of linguistic abilities in children, namely: phonology, semantics, and syntax. From all these components, the children get together. It is at this stage that the sounds of the language begin to play in the child and start babbling while pronouncing the words in phonological acquisition. This study aims to describe how the acquisition of language in the phonological aspect. The type of research used is descriptive qualitative, carried out by knowing the description of the stage of children's language acquisition. The data collection method in this research is the listening method and the proficient method. To carry out this observation method using notes and using recordings. With notes, it can be in the form of questions, while the recording technique is in the form of answers from speakers. Furthermore, from that data as a research source for the acquisition of the first language of children in Java.Â